Potret Pernikahan Dalam Islam - Teguh Prawiro (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2019)
Portrait of marriage institution in Islam is more about sad stories of women in his life. The unfair relationship between men and women is proof in the practice of polygamy, secret marriage, and child marriage. Not infrequently, islamic teachings is only used just about to discuss sex problems. In many places and forums, when religion becomes the subject of conversation, it always comes with the issue of sex. whereas, the purpose of sharia or better known as maqashid al shariah is to realize the benefit of human being.